Analisis Pendapatan Usaha Agroindustri Kue Talam Jagung Manis di Nagari Sungai Antuan Kecamatan Mungka - Mukhlis; Riva Hendriani; Nila Sari; Latifa Hanum; Regia Indah Kemala Sari; Sri Kembaryanti Putri; Amrizal (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2023)
This research is based on the application of innovation, creativity, and differentiation of kue talam by utilising the ample availability of sweet corn by the wants and needs of consumers and producers. This study is based on the application of innovation, creativity, and differentiation of sweet corn talam cakes by utilising the ample availability of sweet corn by the wants and needs of consumers and producers, so that the cakes are attractive and tasty to increase the income of entrepreneurs and corn farmers. This study aims to analyse the business income of sweet corn talam cake agro-industry. To analyse the income of the sweet corn talam cake agro-industry business, it was carried out using quantitative descriptive methods using the income formula. The results showed that: The total cost required in the agro-industrial business of sweet corn talam cake is Rp 1,995,168; The total revenue obtained from the agro-industrial business of sweet corn talam cake is Rp 2,880,000, the amount of income earned is Rp 884,832.